LA DORSALE PALEOCARNICA ANISICA DI PONTEBBA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
The Middle Triassic stratigraphy of the Carnian Range north of Pontebba has been investigated. Aim of the paper was (1) to identify the source area of the carbonate—siliciclastic material which characterizes the whole sequences southwards the Fella—Sava tectonic line and (2) to reconstruct the paleogeographic—structural evolution of the area during the Late Anisian.
Keywords: Stratigraphy; Paleogeography; Dasycladaceae; Upper Anisian; Paleocarnian Range; Pontebba NE Italy.